2022
DOI: 10.1136/bjsports-2022-105825
|View full text |Cite
|
Sign up to set email alerts
|

Transform-Us! cluster RCT: 18-month and 30-month effects on children’s physical activity, sedentary time and cardiometabolic risk markers

Abstract: ObjectiveTo test the efficacy of theTransform-Us!school- and home-based intervention on children’s physical activity (PA), sedentary behaviour (SB) and cardiometabolic risk factor profiles.MethodsA 30-month 2×2 factorial design cluster randomised controlled trial delivered in 20 primary schools (148 Year 3 classes) in Melbourne, Australia (2010–2012), that used pedagogical and environmental strategies to reduce and break up SB, promote PA or a combined approach, compared with usual practice. Primary outcomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In school-aged children, interventions taking a rather innovative approach have been conducted, such as school-based gardening, 93 gamification strategy to nutrition and physical activity, 94 or interventions delivered by class-room teachers. 95 However, only few studies conducted in school-aged children have found intervention effects (for example, other works [94][95][96] ), and the majority of studies have shown no effects of the intervention (for example, previous studies 93,[97][98][99][100][101][102][103] ).…”
Section: Main Findings From Updated Reviewmentioning
confidence: 99%
“…In school-aged children, interventions taking a rather innovative approach have been conducted, such as school-based gardening, 93 gamification strategy to nutrition and physical activity, 94 or interventions delivered by class-room teachers. 95 However, only few studies conducted in school-aged children have found intervention effects (for example, other works [94][95][96] ), and the majority of studies have shown no effects of the intervention (for example, previous studies 93,[97][98][99][100][101][102][103] ).…”
Section: Main Findings From Updated Reviewmentioning
confidence: 99%
“…The results of this RCT are described and interpreted in detail elsewhere. 26 However, in brief, at 18 months (n=348), compared with usual practice, children who received the physical activity intervention (groups PA-I and PA+SB-I) had significantly less weekday sedentary time (−27 min/day). Compared with usual practice, children who received the sedentary behaviour intervention (SB-I and PA+SB-I) spent more time in daily physical activity (5.5 min/day) at 18 months, and at 30 months spent 33 min less in daily sedentary time, and specifically, 63 min less in sedentary time on weekdays, with no differences in physical activity at 30 months.…”
Section: Introductionmentioning
confidence: 95%
“…The efficacy of the initial TransformUs programme was demonstrated in a four-arm two-by-two factorial design cluster-randomised controlled trial (RCT) involving 20 primary (elementary) schools, 226 teachers and over 1600 children in Melbourne, Australia (2010–2013). 26 The three intervention arms targeted either increases in physical activity (PA-I), reductions in sedentary behaviour (SB-I) or a combination of both (PA+SB-I), compared with a usual practice control. The results of this RCT are described and interpreted in detail elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations